Synthesis of Porous MgAl-LDH on a Micelle Template and Its Application for Efficient Treatment of Oilfield Wastewater - Bingbing Bai; Qingchen Wang; Yan Sun; Rui Zhou; Gang Chen; Ying Tang (Molecules, 2023)
In this paper, a series of porous hierarchical Mg/Al layered double hydroxides (named as LDH, TTAC-MgAl-LDH, CTAC-MgAl-LDH, and OTAC-MgAl-LDH) was synthesized by a simple green hydrothermal method using wormlike micelles formed by salicylic acid and surfactants with different carbon chain lengths (0, 14, 16, and 18) as soft templates. BET, XRD, FTIR, TG, and SEM characterizations were carried out in order to investigate the structure and properties of the prepared materials. The results showed that the porous hierarchical CTAC-MgAl-LDH had a large specific surface area and multiple pore size distributions which could effectively increase the reaction area and allow better absorption capability. Benefiting from the unique architecture, CTAC-MgAl-LDH exhibited a large adsorption capacity for sulfonated lignite (231.70 mg/g) at 25 °C and a pH of 7, which outperformed the traditional LDH (86.05 mg/g), TTAC-MgAl-LDH (108.15 mg/g), and OTAC-MgAl-LDH (110.51 mg/g). The adsorption process of sulfonated lignite followed the pseudo-second-order kinetics model and conformed the Freundlich isotherm model with spontaneous heat absorption, which revealed that electrostatic adsorption and ion exchange were the main mechanisms of action for the adsorption. In addition, CTAC-MgAl-LDH showed a satisfactory long-time stability and its adsorption capacities were still as high as 198.64 mg/g after two adsorption cycles.